Comparative analysis of flavonoid metabolites from different parts of Hemerocallis citrina - Hongrui Lv; Shang Guo (BMC Plant Biology, 2023)
Abstract Background Hemerocallis citrina Baroni is a traditional medical and edible plant. It is rich in flavonoid compounds, which are a kind of important bioactive components with various health benefits and pharmaceutical value. However, the flavonoid metabolomics profile and the comparison of flavonoid compounds from different parts of H. citrina is scarce. Results In this study, flavonoid metabolites were investigated from roots, stems, leaves and flowers of H. citrina. A total of 364 flavonoid metabolites were identified by UPLC-MS/MS based widely targeted metabolomics, and the four plant parts showed huge differences at flavonoid metabolic level. Compared to roots, 185, 234, and 119 metabolites accounted for upregulated differential flavonoid metabolites (DFMs) in stems, leaves, and flowers, respectively. Compared to stems, 168 and 29 flavonoid metabolites accounted for upregulated DFMs in leaves and flowers, respectively. Compared to leaves, only 29 flavonoid metabolites accounted for upregulated DFMs in flowers. A number of 35 common flavonoid metabolites were observed among six comparison groups, and each comparison group had its unique differential metabolites. The most abundant flavonoid metabolites in the four parts are flavonols and flavones, followed by flavanones, chalcones, flavanols, flavanonols, anthocyanidins, tannin, and proanthocyanidins. 6,7,8-Tetrahydroxy-5-methoxyflavone, 7,8,3’,4’-tetrahydroxyflavone, 1-Hydroxy-2,3,8-trimethoxyxanthone, Farrerol-7-O-glucoside, 3’,7-dihydroxy-4’-methoxyflavone, 3,3’-O-Dimethylellagic Acid, 5-Hydroxy-6,7-dimethoxyflavone, Nepetin (5,7,3’,4’-Tetrahydroxy-6-methoxyflavone), (2s)-4,8,10-trihydroxy-2-methoxy-1 h,2 h-furo[3,2-a]xanthen-11-one are dominant in roots. Isorhamnetin-3-O-(6’’-malonyl)glucoside-7-O-rhamnoside, 7-Benzyloxy-5-hydroxy-3’,4’-methylenedioxyflavonoid, 3-Hydroxyphloretin-4’-O-glucoside are dominant in stems. Chrysoeriol-7-O-glucoside, Epicatechin glucoside, Kaempferol-3-O-rhamnoside (Afzelin)(Kaempferin)*, Azaleatin (5-O-Methylquercetin), Chrysoeriol-5-O-glucoside, Nepetin-7-O-glucoside(Nepitrin), 3,5,7,2’-Tetrahydroxyflavone; Datiscetin, Procyanidin B2*, Procyanidin B3*, Procyanidin B1, Isorhamnetin-3-O-(6’’-acetylglucoside) are dominant in leaves. kaempferol-3-p-coumaroyldiglucoside, Delphinidin-3-O-sophoroside-5-O-glucoside, Limocitrin-3-O-sophoroside, Kaempferol-3-O-rutinoside(Nicotiflorin), Luteolin-7-O-(6’’-malonyl)glucoside-5-O-rhamnoside are dominant in flowers. Conclusion There was significant difference in flavonoid metabolites among different parts of H. citrina. Leaves had relative higher metabolites contents than other parts. This study provided biological and chemical evidence for the different uses of various plant parts of H. citrina, and these informations are important theoretical basis for the food industry, and medical treatment.